Pengalaman Perempuan Setelah Perselingkuhan Pasangan, bertahan atau berpisah ? : - - -, Indria; Anis Endang , Anis Endang (Universitas Bengkulu, 2022)
The purpose of this study was to examine the experiences of woman after their partner’s infidelity, whether to stay or choose to separate. This study uses a qualitative methode with a phenomenological approach. Data was collected through semi-structured in-dept interviews and informants in this study were selected through purposive techniques based on considerations of suitability with the problem and research abjectives. The informants in this study amounted to two women who were the research subjects with the problem of husband’s infidelity. Based on the result of the study, it can be concluded that in the end the experience of woman who experience infidelity with their partners will shoose to end their housedhold or choosed to separate. Keywords: Woman, infidelity, endure, separate.